Artificial intelligence wrote a fairy tale: simulation of text impact against the background of natural word-containing semiosis - Andrey Vdovichenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология, 2025)
Artificial intelligence (AI) is developed and improved as a "language model" of natural intelligence (NI). A superficial understanding of the relationship between text and meaning-making may be misleading regarding the capabilities and actions of AI. In this article, the AI phenomenon is presented within the framework of a communicative rather than a linguistic paradigm. The theoretical basis of the communicative approach can be considered the concepts of semiotic impact and the cognitive state of a semiotic actor, which are the cause of the generation of signs and meaning-making in natural semiosis (including word-containing, grapheme-containing, or textual). Postulating a system of semantic-formal modules "sign body-meaning" in the linguistic paradigm provokes an incorrect interpretation of the AI phenomenon, as a result of which the sign sequence (text) itself, corresponding to autonomous linguistic rules, becomes a sign of thinking (intelligence). The linguistic interpretation of AI is a problem (misunderstanding of the causes and consequences of AI “speaking”), which is removed by using a communicative approach.